Genealogi kekerasan dan pergolakan subaltern : bara di Bali Utara - Suryawan, I Ngurah, 1980- (Rawamangun, Jakarta, Indonesia : Prenada, 2010)
On political violence in Kabupaten Buleleng, Bali, Indonesia from Hindu and sociocultural perspectives.
Revision of the author's thesis (master's)--Universitas Udayana, Bali, 2008.
Includes bibliographical references (p. [441]-456).
Keywords: Political violence -- Indonesia -- Buleleng (Kabupaten); Buleleng (Indonesia : Kabupaten) -- Politics and government